Feasibility study of the implementation of a deconcentrated and processbased management model in public universities in Ecuador (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
This study aims to determine the feasibility of administrativelyimplementing a deconcentrated and process-based institutionalmanagement model at the University of Guayaquil, as well as theproposal of a management model that allows the execution ofstrategic, business and support processes at the University ofGuayaquil, in order to achieve a significant institutionaltransformation. For this purpose, a survey and analysis of the currentprocess management at the UG was carried out, which allowsproposing to the authorities the tools and mechanisms through whichthe implementation of processes could be made more viable and thuscomply with the Plan of Excellence proposed by the InterventionCommission, which will lead the institution to overcome the Dcategory in which it is currently located.